Viewing Cute Images Does Not Affect Performance of Computerized Reaction Time Tasks - Ziv, Gal; Fox, Orly (Frontiers in Psychology, 2022)
Humans are emotionally affected by cute or infantile appearances, typical of baby animals and humans, which in turn often leads to careful and cautious behavior. The purpose of this pre-registered study was to examine whether looking at cute images of baby pets improves performance of computerized cognitive-motor tasks. Ninety-eight participants were recruited for this online study and were randomly assigned to two experimental groups. The participants in one group performed two cognitive-motor tasks (Simon task and alternate task-switching task) before and after viewing images of adult pets and the participants in the other group performed the tasks before and after viewing images of baby pets. The participants who viewed images of baby pets rated them as significantly cuter (Cohen’s d = 0.50) and more infantile (Coen’s d = 1.56) compared with those who viewed images of adult pets. All participants improved their performance from the pre-test to the post-test, but no differences in correct responses and reaction times were seen between the groups. However, pet ownership appeared to serve as a moderating variable with pet owners performing the Simon task faster than non-pet owners. In addition, pet owners reacted faster in the alternate task-switching task after viewing cute and infantile images but not after viewing images of adult pets. This effect was not found among non-pet owners. In conclusion, this study did not find that viewing cute images improves cognitive-motor performance, yet this may be dependent on moderators like pet ownership.